Enhancing Business Sustainability Through Organizational Resilience and Green Supply Chain Integration: A Mixed-Methods Approach - Zainurrafiqi; Gazali; Hakim, Rachman; Risal, Zef; Retnoningsih, Dwi; Pipatrapa, Anirut; Pawar, Avinash; Effiyaldi (Universitas Brawijaya, Indonesia, 2025)
In a rapidly evolving business environment, firms are increasingly challenged to adapt and innovate to maintain competitiveness. Green supply chain integration has emerged as a strategic approach for firms to align operational processes with sustainability objectives. At the same time, organizational resilience is recognized as a critical capability for navigating environmental and market disruptions. Despite the growing importance of these factors, studies exploring their combined impact on sustainable business performance remain limited. Grounded in dynamic capabilities theory, this study investigates the roles of green competitive advantage and organizational resilience in fostering sustainable performance through an explanatory sequential mixed-methods design. Initially, a quantitative survey involving 450 SME managers in Madura was conducted to empirically test the research model using structural equation modeling (SEM). Subsequently, qualitative interviews with selected managers provided nuanced insights into the mechanisms underpinning these relationships. Findings affirm that green supply chain integration and organizational resilience significantly enhance sustainable business performance, with green competitive advantage serving as a key intermediary that strengthens this relationship. This study demonstrates that embedding green supply chain practices directly into core business strategies improves SMEs' adaptability to environmental changes and increases operational efficiency, providing measurable competitive advantages in dynamic market environments.